COVID-19 and pregnancy: Complications and mortality. - Ibarra, Jose Felix (2022)
The pandemic caused by SARS-CoV-2, which causes the COVID-19 disease, has put the world in vulnerable conditions, leading to an unprecedented global crisis. Pregnant women are a special population that is used to being vulnerable to diseases diagnosed in pregnancy, especially the infectious kind. The objective of this review is to determine the level of risk of maternal mortality and complications in pregnant women exposed to SARS-CoV-2 infection by a literature review in PubMed, Science Direct and ClinicalKey with a systematic search in Pubmed. The result of this review showed that the risk level of SARS-CoV-2 in pregnant women is evidenced in the higher rate of mild, moderate and severe complications compared to the general population. The mortality rate in pregnant women with COVID-19 remains below 2% and in dead pregnant women, previous comorbidities have been reported in 20% in some studies.